2018
DOI: 10.1002/bkcs.11656
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of Dissociation Behavior and Structures of [M·pSer]+ (M = Li, Na, Ag, Rb, and Cs) Complexes

Abstract: Complexes of metal monocations and phosphoserine (pSer) were generated by electrospray ionization (ESI), and were subjected to collision-induced dissociation (CID). The primary fragmentation pathways of [LiÁpSer] + , [NaÁpSer] + , and [AgÁpSer] + are dephosphorylation, dehydration, and Ser residue loss whereas metal ion loss is dominant for [RbÁpSer] + and [CsÁpSer] + . Density functional theory (DFT) calculations suggest a correlation between structures, ion-ligand binding energies, and fragmentation behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…12 The stabilization is also reflected by the Ag + Mulliken charge of + 0.172, indicative of a strong ion–ligand interaction. A comparison of the current result and those in previous studies 1921,24 shows that metal ion size is only one of several factors that can affect the dissociation behavior. The extent of charge transfer to the ligand and the ion–ligand binding energy also play a significant role.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…12 The stabilization is also reflected by the Ag + Mulliken charge of + 0.172, indicative of a strong ion–ligand interaction. A comparison of the current result and those in previous studies 1921,24 shows that metal ion size is only one of several factors that can affect the dissociation behavior. The extent of charge transfer to the ligand and the ion–ligand binding energy also play a significant role.…”
Section: Resultssupporting
confidence: 67%
“…In our previous work, 20,21 we showed that Cu 2+ -bound complexes produce different dissociation products from those that contain alkaline earth metal and other transition metal ions; in the current work, we extend the study to those involving monovalent alkali metal cations and the silver cation, with the latter belonging to the same group (1B) as copper. We observed in our previous study of metal cation–phosphoserine complexes 24 that the Ag + -containing complex produces products that are not observed for complexes containing Li + , Na + , Rb + , and Cs + . This was attributed to a stronger ion–ligand interaction for Ag + than for the alkali metal ions.…”
Section: Introductionmentioning
confidence: 75%